Developmental expression of voltage-gated calcium channels in embryonal carcinoma cells. - Petrof, Elaine O. (University of Ottawa (Canada), 1992)
I have examined the expression of calcium channels in P19 cells to determine how their expression is altered during differentiation into cardiac muscle cells. Colonies of beating muscle cells formed from DMSO-induced differentiation of P19 cells were treated with low concentrations of specific L-type calcium channel blockers and all contractions ceased, implying the existence of functional L-type calcium channels in DMSO-differentiated P19 cells. The expression of the various subunits of the L-type calcium channel was examined by PCR (Polymerase Chain Reaction) and Northern blot analysis. The adult skeletal muscle isoform of the $\alpha$1 subunit was undetectable by PCR; however, Northern blot analysis using the skeletal muscle $\alpha$1 subunit probe revealed the presence of two possible isoforms in P19 cells, with mRNA sizes of 6.5 kb and 13 kb. The cardiac isoform of the $\alpha$1 subunit was found to be expressed in DMSO-treated cells, and the appearance of the cardiac $\alpha$1 subunit mRNA on Northern blots corresponded with the on-set of contractile activity. The $\alpha$1 subunit transcript observed was found to correspond to a 9 kb message which was similar to that identified in adult cardiac muscle. The expression of the other subunits of the L-type calcium channel was also investigated. The skeletal forms of the $\beta$ and gamma subunits were undetectable in P19 cells, whereas the $\alpha$2 subunit was present in DMSO-treated P19 cells as determined by PCR but was undetectable by Northern blot analysis. Northern blot analysis using the $\beta$ subunit probe indicated the presence of a weakly related transcript in P19 cells. These results indicate that unique subunits of the L-type calcium channel may be expressed in P19 cells. (Abstract shortened by UMI.)
Keywords: Biology, Molecular.